PERAN PENTING MANAJEMEN KEUANGAN DI SDN GEDONG DALEM 01 KOTA CILEGON UNTUK MENCAPAI KEUNGGULAN PENDIDIKAN - Junaesih, R.; Yusuf, Furtasan Ali; Hayadi, B. Herawan; Rahmulyana, Anjar; Raman, Raman; Yustiva, Fitriyatul (Yayasan Education and Social Center, 2024)
This research explores the important role of financial management in achieving educational excellence at SDN Gedong Dalem 01, Cilegon City. Using qualitative and quantitative approaches, this research analyzes school financial data and conducts in-depth interviews with key stakeholders to understand the impact of effective financial management on the quality of education. The research results show that transparency, efficiency and wise allocation of funds are important factors in improving the quality of education in these schools. These findings are consistent with previous research which confirms the importance of good financial management in achieving educational goals. Practical implications of this research include the need to expand managerial and financial capacity for school staff through training and technical support. This research makes a significant contribution in strengthening understanding of the relationship between school financial management and the achievement of educational excellence, as well as providing direction for concrete efforts to improve managerial and financial capabilities at the school level